2006
DOI: 10.1523/jneurosci.3731-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Dependent Auditory Tuning Results in Synchronous Population Coding of Vocalizations in the Songbird Midbrain

Abstract: Physiological studies in vocal animals such as songbirds indicate that vocalizations drive auditory neurons particularly well. But the neural mechanisms whereby vocalizations are encoded differently from other sounds in the auditory system are unknown. We used spectrotemporal receptive fields (STRFs) to study the neural encoding of song versus the encoding of a generic sound, modulationlimited noise, by single neurons and the neuronal population in the zebra finch auditory midbrain. The noise was designed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
151
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 86 publications
9
151
0
Order By: Relevance
“…The lateral asymmetries suggest that conspecific vocalizations either engage different network properties in each hemisphere or trigger a gating process that routes information differentially to each hemisphere. With respect to the latter possibility, it has been suggested that asymmetrical inhibitory influences in the brainstem auditory system may contribute to lateral differences in the mammalian cortex (17) and that sound context changes tuning functions in the brainstem auditory system of a songbird (18). However, neither the mechanism nor the functional meaning of the lateral differences in ARM's and adaptation rates can be determined from the present experiments.…”
Section: Discussionmentioning
confidence: 62%
“…The lateral asymmetries suggest that conspecific vocalizations either engage different network properties in each hemisphere or trigger a gating process that routes information differentially to each hemisphere. With respect to the latter possibility, it has been suggested that asymmetrical inhibitory influences in the brainstem auditory system may contribute to lateral differences in the mammalian cortex (17) and that sound context changes tuning functions in the brainstem auditory system of a songbird (18). However, neither the mechanism nor the functional meaning of the lateral differences in ARM's and adaptation rates can be determined from the present experiments.…”
Section: Discussionmentioning
confidence: 62%
“…Many neurons in field L, the avian analog of primary auditory cortex, are tightly tuned in time (Nagel and Doupe 2008), causing them to respond to syllable onsets with precisely time-locked spikes (Woolley et al 2006). This temporal pattern of spiking provides significant information about what song was heard (Narayan et al 2006), and several papers have therefore suggested that these temporal patterns of spiking are critical for birds' discrimination and recognition of songs (Larson et al 2009;Wang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The neural representation of songs-particularly in the primary auditory area field L Margoliash 1992, 1995;Vates et al 1996)-has been studied in detail Doupe 2006, 2008;Narayan et al 2006;Sen et al 2001;Theunissen et al 2000;Wang et al 2007;Woolley et al 2005Woolley et al , 2006Woolley et al , 2009. Most field L neurons are highly tuned in frequency, time, or both (Nagel and Doupe 2008;Woolley et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We then turned to the modified spike-triggered average or spike-triggered covariance (mSTA/STC) method for comparison with PPR. The mSTA/STC analysis for natural stimuli have been described previously (21,(56)(57)(58). For comparison, we constructed the RF models by mSTA/STC with the same number of subunits as those from PPR for each cell.…”
Section: Methodsmentioning
confidence: 99%